Performance Degradation Analysis-Based Fatigue Reliability Modeling and Assessment for Offshore Wind Turbine Blade Adhesive Bonding - Liu, Zheng; Shao, Zhenjiang; Li, Yongjie; Liu, Haodong; Liang, Jinlong (IEEE transactions on reliability, 2025)
With cyclic loads and multiple environmental stress factors present, the adhesive performance of offshore wind turbine blades degrades progressively. Previous studies have mainly concentrated on the probabilistic aspects of the adhesive fatigue properties of wind turbine blades, neglecting the fact that adhesive fatigue failure results from a gradual decline in adhesive performance because of the accumulation of progressive fatigue damage. Consequently, by utilizing performance degradation analysis theory, this study introduces a technique for modeling and appraising fatigue reliability while considering the effect of environmental stress on fatigue life. Specifically, the quantification of fatigue performance degradation was accomplished by measuring the cumulative damage. Incorporating a multiple environmental degradation factor, this study employs the cyclic cohesive zone model to scrutinize fatigue damage within the context of combined environmental stress influences. The fatigue performance degradation trajectory is depicted using multistage Wiener processes, followed by an assessment of the fatigue reliability. This study offers comprehensive methodologies for conducting fatigue analyses and predicting the remaining life of the composite single lap joints of offshore wind turbine blades.